Livin' by Mandiri Sebagai Strategi Pemasaran PT. Bank Mandiri - Juliana, Eka; Riofita, Hendra (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
This study examines the marketing strategies implemented by PT. Bank Mandiri through the Livin' by Mandiri application to increase the number of users of digital banking services. Between 2022 and 2024, the number of Livin' by Mandiri users rose from 15.8 million to 27 million, indicating significant growth. The research finds that the success of Bank Mandiri's marketing strategy lies in the innovation of application features, digital promotions, and ongoing service transformation. By focusing on meeting customer needs, Bank Mandiri has successfully built trust and enhanced customer satisfaction, establishing itself as one of the leading financial applications in Indonesia. This study aims to provide insights for other financial institutions in developing effective marketing strategies in the digital era